Pentingnya mengembangkan ketrampilan mendengarkan efektif dalam konseling - Siti Aminah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The communication skills in counseling sessions can support the success of counseling. One of the basic counseling skills is listening skills. Through listening skills, the counselor can understand and interpret the message conveyed by the counselee. In addition, through listening to the counselor, it can provide an appropriate and proper response, hence, it increases trust, comfort, and provide support to the counselee to tell more about the problems they experienced.Listening is effective to help counselors display empathy built in the counseling process. In practice, listening to the counselor has some potential hindrances to listening, it includes 1) having preconceived notions about the client that interfere with the counselor's ability to hear the client, (2) anticipating what the client is about to say and not actually hearing the client, (3) thinking about what you are going to say and therefore blocking what the client is saying, (4) having personal issues that interfere with your ability to listen, (5) having a strong emotional reaction to your client's content and therefore not being able to hear the client accurately, and (6) being distracted by such things as noises, temperature of the office, or hunger pains. In counselling skills, effective listening is one of the important skills to be developed as a basic ability to build throughout the counseling relationships and help to show empathy and provide the right respons.